2017
DOI: 10.1111/ppc.12238
|View full text |Cite
|
Sign up to set email alerts
|

Improving the therapeutic relationship in inpatient psychiatric care: Assessment of the therapeutic alliance and empathy after implementing evidence-based practices resulting from participatory action research

Abstract: The results confirm the possibility of measuring and improving the therapeutic relationship in psychiatric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…2018), and nurses report greater job satisfaction, leading to fewer sick days (Moreno‐Poyato et al . 2018), which reduces the use of costly agency nurses who are unfamiliar to service users and the wards. Conversely, poor engagement is associated with increased levels of violence and aggression (Chaplin et al .…”
Section: Introductionmentioning
confidence: 99%
“…2018), and nurses report greater job satisfaction, leading to fewer sick days (Moreno‐Poyato et al . 2018), which reduces the use of costly agency nurses who are unfamiliar to service users and the wards. Conversely, poor engagement is associated with increased levels of violence and aggression (Chaplin et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the field of mental health, nursing studies have shown that the incorporation of evidence‐based practice in clinical practice increases the empathy of nurses and improves the factors that contribute towards establishing a therapeutic alliance with patients (Moreno‐Poyato et al., 2018), and increasing the nurses' self‐confidence, allowing them to reflect on their practice, present ideas and acquire new knowledge (Moreno‐Poyato et al, 2019). However, these studies have not specifically evaluated the contribution between the EBP and its dimensions and the therapeutic relationship from a quantitative point of view (Moreno‐Poyato et al, 2019; Moreno‐Poyato et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Empathy is a critical component of these therapeutic nurse-patient relationships. 5,18 When the existing empathy scales used in Turkey were examined, it was determined that valid and reliable tools were needed to evaluate empathy multidimensionally. The MDEES developed by Caruso and Mayer 11 is an important tool that can satisfactorily meet this requirement.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Empathic skills are critically important in the establishment of effective communication between individuals and the ability to understand the thoughts and emotions of others. 5 First learned during vocational training and improved through practice and experience over time, empathic skills are used during interventions to determine the problems of others, understand their inner worlds, and collect valuable information from them to the greatest extent possible. 6,7 Empathy is one of the main characteristics that nurses should possess as members of the healthcare field and the general community.…”
Section: Introductionmentioning
confidence: 99%